2020
DOI: 10.5397/cise.2020.00206
|View full text |Cite
|
Sign up to set email alerts
|

PHILOS plate fixation with polymethyl methacrylate cement augmentation of an osteoporotic proximal humerus fracture

Abstract: PHILOS plate fixation in osteoporotic proximal humerus fracture of old age is well-known for high complication rate, especially metal failure, providing various augmentation techniques, such as calcium phosphate cement, allogenous or autologous bone graft. We report a case of PMMA augmentation to provide appropriate reduction with a significant mechanical support. This can be a treatment option for displaced unstable osteoporotic proximal humerus fracture with marked bony defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…A comparative study by Shen et al [17] reported that placement of the medial support screw greatly reduced the screw cutting, varus deformity, and the probability of secondary surgery. Various methods are used to compensate for the effect of the medial support screw and strengthen medial support in clinical practice, such as autologous or allogeneic fibula implantation, titanium mesh implantation, and the use of an auxiliary steel plate [7][8][9][10][11]. The selection, treatment, and placement of fibula grafts and titanium mesh require high technical experience among orthopedic doctors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study by Shen et al [17] reported that placement of the medial support screw greatly reduced the screw cutting, varus deformity, and the probability of secondary surgery. Various methods are used to compensate for the effect of the medial support screw and strengthen medial support in clinical practice, such as autologous or allogeneic fibula implantation, titanium mesh implantation, and the use of an auxiliary steel plate [7][8][9][10][11]. The selection, treatment, and placement of fibula grafts and titanium mesh require high technical experience among orthopedic doctors.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods for strengthening medial support in clinical practice, such as allograft fibula implantation [7], titanium mesh implantation [8], bone cement [9], and auxiliary support plates [10][11]. In clinical practice, the authors have used a 1/3 tubular steel plate as an auxiliary plate to develop the shape according to the lateral anatomical structure of the internodal sulcus, placing it on the outside of the internodal sulcus.…”
mentioning
confidence: 99%
“…A comparative study by Shen et al [17] reported that placement of the medial support screw greatly reduced screw cutting, varus deformity, and the probability of a secondary surgery. In clinical practice, various methods such as autologous or allogeneic fibula implantation, titanium mesh implantation, and the use of an auxiliary steel plate are used to compensate for the effect of the medial support screw and strengthen medial support [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, several methods, such as allograft fibula implantation [7], titanium mesh implantation [8], bone cement [9], and auxiliary support plates [10][11], are used for strengthening the medial support. Authors have used a 1/3 tubular steel plate as an auxiliary plate to develop a shape according to the lateral anatomical structure of the internodal sulcus, placing the plate on the exterior of the internodal sulcus.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, several methods are used to strengthen medial support, such as allograft fibula implantation [ 7 ], titanium mesh implantation [ 8 ], bone cement [ 9 ], and additional steel plate support plates [ 10 , 11 ]. Using a 1/3 tubular steel plate as an additional steel plate shaped according to the lateral anatomical structure of the intertubercular sulcus, the authors have developed a method in which the plate is placed on the lateral of the intertubercular sulcus.…”
Section: Introductionmentioning
confidence: 99%